2023
DOI: 10.3390/rs15112709
|View full text |Cite
|
Sign up to set email alerts
|

Recent Active Fires in Indonesia’s Southern Papua Province Caused by El Niño Conditions

Abstract: This study was conducted to identify the fire weather conditions needed to assess future peatland fires under climate change. Recent peatland fires in Indonesia have resulted in globally significant environmental impacts. Nevertheless, diurnal fire weather in the peatlands has not been clarified. The objective of this study was to determine the fire weather conditions needed to assess future peatland fires under climate change. An analysis of fire weather using diurnal weather data during the most active fire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For Papua fires, we suggested "sea surface temperature anomaly (SSTA)" as a good fire-related index [20]. We found that the SST around Papua (the Northern Arafura Sea) differs significantly between El Niño and La Niña years.…”
Section: Fire-related Index In Papuamentioning
confidence: 88%
See 4 more Smart Citations
“…For Papua fires, we suggested "sea surface temperature anomaly (SSTA)" as a good fire-related index [20]. We found that the SST around Papua (the Northern Arafura Sea) differs significantly between El Niño and La Niña years.…”
Section: Fire-related Index In Papuamentioning
confidence: 88%
“…There are few studies on fire weather conditions and fire-related indices for peatland fires in Indonesia. Because of this, we examined the applicability of PWV to other two fires in Papua [20] and Central Kalimantan [21]. In addition to atmospheric conditions, soil side (peat) conditions were also considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations